Analisis Akuntansi Istishna : Teori, Aplikasi, dan Pengaruh terhadap Laporan Keuangan Syariah - Nurul Inayah; Faidatus Syiriah; Siti Zakia Khalidah Ma`ruf; Falda Nabila Fauziyah; Mukhlishotul Jannah (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
Istishna accounting holds a crucial position in Islamic financial practices as it ensures fairness, transparency, and compliance with Sharia principles in recognizing and measuring costs. Istishna, a unique contract for producing goods based on specific orders, emphasizes the prohibition of uncertainty (gharar) and speculation (maysir), aligning financial activities with ethical and moral values. This article delves into the theoretical foundations of istishna accounting, analyzes its implementation in Islamic financial institutions, and evaluates its impact on financial reporting standards. By integrating Sharia principles with modern financial systems, the study highlights how Islamic financial institutions can maintain accountability and integrity while fostering trust among stakeholders. Furthermore, the article discusses challenges such as adapting to dynamic regulatory changes and balancing business needs with Sharia compliance. This research offers practical recommendations to enhance the credibility and relevance of Islamic financial statements, ensuring their alignment with global economic demands while upholding ethical standards.